Effects of age on fall risk index among women in Klang Valley / Nurul Nadiah Shahudin - Shahudin, Nurul Nadiah (2013)
This study investigates the effects of age on fall risk index among women in Klang Valley area. This study focused on four variables which is age, physical activity level, strength and balance. The present study was also conducted to determine the main contributing factors to the fall risk index between the four variables. Two hundred women age ranged between 20-73 years old participated in this study. Body strength was assessed using handgrip dynamometer test while balance performance and fall risk index was assessed using postural static balance programme of Biodex Balance Machine. Regression analysis was conducted to indicated the main contributing factor towards in fall risk index (p <0.05). Age (54.9%) contributed the most compared to physical activity, strength and balance. Results indicated that, fall risk index increased as they age because participants physical activity level were at moderate level, but women who are physically active were stronger in muscle with statistically significant different at each age decade. The balance component also indicates the significant dropping occurs at forties (25.42%). In conclusion, result suggested that women in Klang Valley aged 20 to 73 were found to associate with fall risk index and three important aspects, age, physical activity, strength and balance.